LOW DENSITY, LOW COMPRESSION SET, LONG RECOVERY TIME POLYURETHANE FOAM (2020)
Flexible polyurethane foams are characterized in having slow recovery times, low foam densities and very low compression sets. The foams are useful in human comfort applications such as pillows and mattresses.